The effectiveness of positivism training with an Islamic approach on self-control, self-compassion, and the other dyadic perspective taking in married women - Khatami , Fatemeh sadat; Zanganeh , Firoozeh (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The present study aimed to determine the effectiveness of positivism training, with an Islamic approach, on self-control, self-compassion, and the other dyadic perspective-taking in married women. Method: The research method was quasi-experimental with experimental and control groups, a pre-test, post-test design, and a two-month follow-up. The statistical population consisted of 5606 married female students at Azad University of Arak in 2020, among whom we selected 30 married students using convenience sampling and randomly assigned them to experimental and control groups. We conducted the positivism training program with an Islamic approach in eight 60-minute sessions for the experimental group. We evaluated the data using the Self-Control Scale (2004) by Tangney et al., the Neff self-compassion scale (2003), and Long's other dyadic perspective-taking Scale (ODPT (1990) at three stages, pre-test, post-test, and follow-up. We analyzed the data using repeated measures mixed model analysis of variance (ANOVA). Results: The results indicated the effects of positivism training with an Islamic approach on self-control (p=0.038 and F= 12.659), self-compassion (p=0.0.041 and F= 6.884), and the other dyadic perspective-taking (p=0.038 and F= 14.58), and the stability of the effect at the follow-up stage. Conclusion: The results indicated that positivism training with an Islamic approach affected self-control, self-compassion, and other dyadic perspective-taking in married women.